Heterosis and combining ability analysis for yield and its component traits in Indian mustard (Brassica juncea) - SHEKHAWAT, NEELAM; SHARMA, HEMLATA; CHANDRAWAT, K S (The Indian Journal of Agricultural Sciences, 2022)
Ten diverse lines of Indian mustard [Brassica juncea (L.) Czern. & Coss.] were crossed in diallel mating design excluding reciprocals during winter (rabi) season 2014–15 to study heterosis and combining ability. The mean squares due to genotypes including parents, crosses and parents vs. crosses were significant for all the traits. The analysis of variance revealed significant mean sum of squares of general combining ability (GCA) and specific combining ability (SCA) for most of the characters at all three environments, except mean sum of squares due to GCA for length of siliqua in E3 environment and mean sum of squares due to SCA for plant height in E1 and for number of secondary branches per plant in E3 environment. In pooled analysis, mean squares due to GCA, SCA, GCA × E and SCA × E were significant for all the eight characters except SCA × E for plant height and GCA × E for protein content. The estimates of GCA effects revealed that parents, viz. Pusa Vijay, PM-30 and Bio-902 were good general combiners for yield contributing traits and the best specific cross combinations for yield and its attributing traits were PM-27 × RGN-229, PM-27 × RGN-73, Pusa Vijay × Laxmi, Pusa Vijay × DRMR-IJ-31 and Pusa Vijay × RGN-73 on the basis of pooled analysis. The crosses Bio-902 × RGN-48, PM-30 × Bio-902 and Bio-902 × RGN-73 exhibited highest and positive significant heterotic effects for seed yield per plant and its important component traits. These F1s may be exploited for obtaining transgressive segregants for development of hybrid varieties in Indian mustard.